2015
DOI: 10.1016/j.ajo.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis of SIX1-SIX6 With Retinal Nerve Fiber Layer Thickness in Individuals of European Descent

Abstract: Purpose To perform a quantitative trait locus (QTL) analysis and evaluate whether a locus between SIX1 and SIX6 is associated with retinal nerve fiber layer (RNFL) thickness in individuals of European descent. Design Observational, multi-center, cross-sectional study. Methods 231 participants were recruited from the Diagnostic Innovations in Glaucoma Study and the African Descent and Glaucoma Evaluation Study. Association of rs10483727 in SIX1-SIX6 with global and sectoral RNFL thickness was performed. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 48 publications
9
29
1
Order By: Relevance
“…These results were consistent with previous candidate SNP evaluations on rs33912345 3032 . In addition, our findings suggest that the 32-sector region-based approach for cpRNFLT enables the detection of underpowered and undermined genetic associations in 4-sector analyses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results were consistent with previous candidate SNP evaluations on rs33912345 3032 . In addition, our findings suggest that the 32-sector region-based approach for cpRNFLT enables the detection of underpowered and undermined genetic associations in 4-sector analyses.…”
Section: Discussionsupporting
confidence: 92%
“…This is the only locus where an association with cpRNFLT has been established 3032 . In this study, our detailed analysis further specified the cpRNFL region of association, and revealed that SIX1/SIX6 affects cpRNFL thinning at 281.3–303.8° among the inferior region, which may have clinical and biological relevance since retinal nerve fibre layer defects also occur in this region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several subsequent studies have also confirmed that the SIX1/SIX6 locus was significantly correlated with POAG and VCDR in different independent ethnic cohorts (Burdon et al, 2015;Chen et al, 2015;Fan et al, 2011;Iglesias et al, 2014;Mabuchi et al, 2015;Osman et al, 2012b;Philomenadin et al, 2015;Ramdas et al, 2011;Wiggs et al, 2012), but the association has not yet been demonstrated in African cohorts owing to the high frequency of the risk allele both in patients and controls (Liu et al, 2013;Williams et al, 2015). Recently, two population-based studies using cohorts from Singapore and of European-descents showed that both glaucomatous and nonglaucomatous subjects with risk allele variants in the SIX1/SIX6 locus (rs10483727 and rs33912345) were susceptible to thinner retinal nerve fiber layer thickness, which confirmed the results of previous studies (Carnes et al, 2014;Cheng et al, 2015;Kuo et al, 2015). Our results that both rs33912345 and rs10483727 were strongly associated with NTG and POAG were consistent with the findings of a previous association study also based on the Chinese population (Chen et al, 2015).…”
Section: Discussionsupporting
confidence: 75%